I was looking for a street - Willeford, Charles Ray 1919-1988 (Orion Books, 2015)
"'I was looking for a street' tells the story of Charles Willeford's childhood and adolescence as, orphaned, he moved from railroad yard to hobo tent city to soup kitchen and desert around Los Angeles, and across the United States. The tale is at once a picaresque adventure through Depression-era America and a portrait of the writer as a young man of apparently little promise but great spirit. Written late in Willeford's career, this memoir is the work of a writer at the height of his powers, looking back without nostalgia or regret, and preserving in his clear and forceful prose the great American adventure of his youth." (Buchrückseite)
Keywords: Willeford, Charles Ray / 1919-1988; Authors, American / 20th century / Biography; Tramps / United States / Biography; Los Angeles (Calif.) / Social life and customs; Écrivains américains / 20e siècle / Biographies; Vagabonds / États-Unis / Biographies; Manners and customs; California / Los Angeles; Authors, American; Tramps; United States; 1900-1999; Biographies; Autobiografie